Pengaruh Tata Kelola Kolaboratif terhadap Keberhasilan Program Pembangunan Berkelanjutan di Kawasan Pesisir Makassar - Natsir Mallawi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Sustainable development in coastal areas requires collaborative governance involving multiple stakeholders, including government, private sector, and communities. Makassar, as a major coastal city in Eastern Indonesia, faces significant challenges in implementing sustainable development programs in its coastal areas.This study examines the influence of collaborative governance on the success of sustainable development programs in Makassar's coastal areas, with a focus on accountability mechanisms and stakeholder engagement processes.This research employs a mixed-method approach, combining quantitative analysis using Structural Equation Modeling (SEM) and qualitative analysis through in-depth interviews with 150 respondents from government agencies, private sector, NGOs, and local communities. Data were collected from January to October 2024 in four coastal sub-districts of Makassar.The study reveals that collaborative governance significantly influences the success of sustainable development programs (β = 0.687, p < 0.001). Key mediating factors include transparency in resource allocation (β = 0.445, p < 0.01), community participation in decision-making (β = 0.523, p < 0.001), and integrated monitoring systems (β = 0.398, p < 0.05). Effective collaborative governance enhances sustainable development program outcomes through improved accountability, resource efficiency, and stakeholder satisfaction. The findings suggest that formal collaboration frameworks and transparent financial reporting mechanisms are critical success factors.